Transnationalisation of national peasants movements' activism: the case of the National Union of Small-scale Farmers of Mozambique's membership to La Via Campesina - Guilengue, Fredson Guirramela Lopes (My University, 2017)
In this master's dissertation report, I explore how the National Union of Small-scale Farmers of Mozambique (UNAC) transnationalised its activism through its membership to La Via Campesina (LVC), covering the period between 2004 and 2014, to understand the nature of transnational activism of national peasant movement organisations. I identify the factors behind national peasant movement organisations embarking on transnational activism, the structure put in place to secure their transnational activism and the possible opportunities and threats transnational activism poses to their national mandate. I applied ethnography and more concretely Michael Burawoy's approach to the extended case method to reconstruct (by extending) neo-Marxist approaches to the study of peasantry, peasant movements and social movements in general. Based on a qualitative approach to the data collected, the research conducted documentary analysis and in-depth interviews with relevant actors. Results suggest that peasants' national movement organisations transnationalise part of their activism through joining an already transnational peasant's movement organisation by adopting and campaigning for its political themes, building transnational peasant activists, and by practising transnational solidarity. Results also suggest that national peasant movement organisations transnationalise their activism precisely because they share a common interest of fighting capitalism with the movement organisation they affiliate with, they seek to expand their political messages and because they are looking for international solidarity. Added to this, results show that this type of transnational activism does not necessarily require specific administrative structures and does not pose major threats to the national mandate of national peasant movement organisations. More importantly, results suggest re-theorising the neo Marxists' approach to social movements by accommodating transnational agency of national peasant movement organisations.
A research report submitted in fulfilment of the requirements for the degree of Masters of Arts by Research (Development Studies) to the Faculty of Humanities, University of the Witwatersrand, 2017